An exotic collembolan genus and species (Isotomidae: Anurophorinae) new for New Zealand. Issue 1 (2nd January 2019) - Greenslade, Penelope
ABSTRACT: This paper records an exotic collembolan the species, Anurophorus laricis Nicolet, 1842, found for the first time in New Zealand. Its specific identity is confirmed using morphological data. The record is significant because it is the first for the genus Anurophorus in the Southern Hemisphere. Moreover, the species was found fairly abundantly on the native shrub, manuka, at 300 m asl, an unusual habitat for an exotic species. The high number of exotic, mainly European but also North American, species identified on morphological grounds found in Australia and New Zealand, has not in the past been accepted as valid by taxonomists in Europe. Confirmation using molecular sequence data has only recently been possible and was attempted but was not successful. A related issue is that there has been a trend of Salmon's New Zealand endemic isotomids, both genera and species, being recognised as exotic after revision. We propose likely attributes of species and habitats that facilitate colonisation of exotic species in New Zealand which should help conservation efforts to be well focused.